The tomato SlSHINE3 transcription factor regulates fruit cuticle formation and epidermal patterning. Issue 2 (3rd December 2012) - Shi, Jian Xin; Adato, Avital; Alkan, Noam; He, Yonghua; Lashbrooke, Justin; Matas, Antonio J.; Meir, Sagit; Malitsky, Sergey; Isaacson, Tal; Prusky, Dov; Leshkowitz, Dena; Schreiber, Lukas; et al.
Summary: Fleshy tomato fruit typically lacks stomata; therefore, a proper cuticle is particularly vital for fruit development and interaction with the surroundings. Here, we characterized the tomato SlSHINE3 (SlSHN3) transcription factor to extend our limited knowledge regarding the regulation of cuticle formation in fleshy fruits. We created SlSHN3 overexpressing and silenced plants, and used them for detailed analysis of cuticular lipid compositions, phenotypic characterization, and the study on the mode of SlSHN3 action. Heterologous expression of SlSHN3 in Arabidopsis phenocopied overexpression of the Arabidopsis SHNs . Silencing of SlSHN3 results in profound morphological alterations of the fruit epidermis and significant reduction in cuticular lipids. We demonstrated that SlSHN3 activity is mediated by control of genes associated with cutin metabolism and epidermal cell patterning. As with SlSHN3 RNAi lines, mutation in the SlSHN3 target gene, SlCYP86A69, resulted in severe cutin deficiency and altered fruit surface architecture. In vitro activity assays demonstrated that SlCYP86A69 possesses NADPH‐dependent ω‐hydroxylation activity, particularly of C18:1 fatty acid to the 18‐hydroxyoleic acid cutin monomer. This study provided insights into transcriptional mechanisms mediating fleshy fruit cuticle formation and highlighted the link between cutin metabolism and the process of fruit epidermal cell patterning.